Guduchi fibres (Tinospora cordifolia Linn.) as a skin suturing material - A Controlled Clinical Trial: Array - Shrestha, Monica; Jagdhane, C. D.; Dudhamal, Tukaram (Ayurline: International Journal of Research in Indian Medicine, 2017)
Sushruta mentioned sivana using different suture material made from plant and animal origin. Guduchi is one among the plant origin suture materials.Skin suturing is an integral part of surgery technique tokeep minimum scar. Suturing consists of ensuring good adaptation of body tissues for proper wound healing .For that purpose, choice of suturing material play important role equally to good technique. In this study an attempt has been made to address Guduchi as suturing material for skin suturing in post operative and traumatic wounds. The 60 patients of post operative and traumatic fresh wounds were selected from OPD and IPD of ShalyaTantra and randomly divided into two groups using computerised randomisation tables. In trial group (n=30) patients were treated with suturing by innovative Guduchi fibres and in control group (n= 30) patients were treated with suturing by conventional cotton thread. Assessment was done on basis of subjective and objective criteria. The trial group showed good results in parameters like pain, oedema while no difference was observed in criterias like restoration of daily work, discharge and days taken for wound healing. This study illustrated that Guduchi or Tinospora cordifolia stem fibers can be made an acceptable suturing material and it can be used safely in skin suturing. Guduchi sutures can be used as a safe alternative for cotton thread in skin closure.